STUDENTS’ PERCEPTION ON THE USE OF MIND MAPPING APPLICATION SOFTWARE IN LEARNING WRITING - Rahmad Fadillah (University of Muhammadiyah Malang, 2019)
The aim of this research is to investigate the students’ perception on the use of Mind Mapping in learning writing. Mixed method was employed to describe the students’ perception on the use of Mind Mapping in learning writing and the advantages and disadvantages of Mind Mapping in learning writing. The researcher took class B who joined writing IV class in academic years 2014 as the research subjects. This research used questionnaire and interview as the instruments for collecting the data. Moreover, The research findings showed that there were positive and negative perception on the use of Mind Mapping in learning writing. The majority of the students had positive perception on the use of Mind Mapping in learning writing and they perceived that Mind Mapping is an effective way to help them to organize the ideas in learning writing. Furthermore, the use of Mind Mapping in learning writing gives three advantages, namely: (1) Mind Mapping eased the students to think and organize their ideas before writing something; (2) it facilitated the students to develop their ideas and (3) it helped the students remember better about the ideas. The findings also showed two disadvantages, namely: (1) Mind Mapping took longer time to create and organize the ideas; and (2) it needed computer access to create a Mind Mapping.